Synthesis of TiO2 nanoribbons and its application in photoelectrochemical water splitting for hydrogen production - Dubey P.K.; Tiwari R.S.; Srivastava O.N.; Sinha A.S.K. (My University, 2025)
In the present investigation nanoribbons of TiO2 were prepared through the hydrothermal process. In a typical preparation procedure, 2 g of TiO2 powder (average size 100 μm) was added to 50 mL of 10 M NaOH and stirred for 10 min in a beaker. The mixture was then transferred into a teflon lined stainless steel autoclave and heated to 150°C for 48 h. After the autoclave was naturally cooled to room temperature, the obtained sample was filtered and washed several times with distilled water and 0.1 M HCl until the pH value of the solution reached to 7 and then the sample was filtered and dried at 80°C for 8 h. To improve the crystallinity the as dried sample was annealed at 500°C for 4 h. The TiO2 nanoribbons were characterized by SEM, TEM, XRD and UV-Visible spectroscopy. The TiO2 nanoribbons have been used for photoelectrochemical hydrogen production in photoelectrochemical solar cells. © 2011 World Scientific Publishing Company.